The determine factor on satisfaction among tourist Visiting sustainable heritage tourism development in Kelantan - Iza Shahfika Ibrahim; Khairul Azmi Murir; Leong Hui Thin; Lim Shin Ying (2023)
This study is measuring the factors that determine the level of sustainability of environmental, economic, socio-cultural and institutional among tourists visiting sustainable heritage tourism development in Kelantan. The problem is determining the carrying capacity can effectively solve the problem of the decline in the cultural identity of historical relics caused by mass tourism. The objective of this study is to see if there is a link between environmental sustainability, economic sustainability, socio-cultural sustainability, institutional sustainability and tourists visiting sustainable heritage tourism development in Kelantan. This study used a quantitative survey of tourists who visited heritage places in Kelantan and used the Statistical Package for Social Sciences (SPSS) to collect the data of respondents. A total of 207 respondents participated to answer all questions in this survey. Environmental sustainability, economic sustainability, socio-cultural sustainability, and institutional sustainability have significant relationships with tourist satisfaction. So, all the hypotheses are supported. Therefore, this study aims to maintain the sustainability of heritage places in Kelantan and disclose to the public about the advantages of heritage places in Kelantan. Thus, it brings satisfaction to all visitors. Keywords: Heritage, Environmental sustainability, economic sustainability, socio-cultural sustainability, institutional sustainability, tourist satisfaction.